Audit Company Performance : The Impact of Ownership Structure and Committee - Swastya, Decipta Eka; Putra, Raja Adri Satriawan; Rofika, Rofika; Putra, Ferdy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Abstract This study aims to analyze the impact of management ownership, institutional ownership, foreign ownership, audit committee size, meeting frequency, and ownership on corporate performance. The relationship between ROA and Tobin's Q is used to gauge company performance. The manufacturing businesses registered on the Indonesia Stock Exchange in 2019–2021 make up the study's population. 44 businesses were sampled using the principles of purposive sampling. Multiple linear regression analysis was performed for data analysis. The findings demonstrated that, when considering ROA rather than Tobin's Q, the size of the audit committee had an impact on corporate performance. Both corporate performance metrics are impacted by the volume of audit committee sessions. Managerial ownership has an impact on company performance when Tobin's Q is used to measure performance rather than ROA, which has no effect. While it has no impact on company performance when using Tobin's Q measurement, institutional ownership has an impact on ROA-based measures of firm performance. Foreign ownership has no impact on firm performance as assessed by ROA, but it does have an impact on firm performance using Tobin's Q measurement. Keywords: size of the Audit Committee, Audit Committee meetings, managerial ownership, institutional ownership, foreign ownership, earnings quality